Enhanced production of thermostable lipase from Bacillus cereus ASSCRC-P1 in waste frying oil based medium using statistical experimental design - Ghada E. A. Awad, Hanan Mostafa, Enas N. Danial, Nayera A.M. Abdelwahed, Hassan M. Awad (Journal of Applied Pharmaceutical Science, 2015)
This study aim to isolate, identify a bacterial isolate and optimize production medium using frying oil waste for lipase production. Nine strains were isolated from an Egyptian soil samples. Among the isolates, a potent bacterial candidate ASSCRC-P1 was found to be the most potent lipase producer strain at 60 °C. Genotypic identification of ASSCRC-P1 showed 94% similarity with Bacillus sp. strains. Phylogenetic tree confirmed that ASSCRC-P1 was nearly similar to Bacillus cereus. Therefore, it was given the name Bacillus cereus ASSCRC-P1 and its 16S rRNA nucleotide has been deposited in the GenBank Data Library under the accession number: KJ531440. A sequential optimization strategy, based on statistical experimental designs, was employed to enhance the lipase production by this strain. A 2-level Plackett–Burman design was applied to differentiate between the bioprocess parameters that significantly influence lipase production followed by Box-Behnken design to optimize the amounts of variables which have the highest positive significant effect on lipase production. Overall more than 2.15-fold improvement in lipase production was achieved due to optimization compared to that obtained using the basal medium.
Keywords: Isolation and genotypic identification, Thermostable lipase, Waste frying sunflower oil, Bacillus cereus ASSCRC-P1, Statistical designs.